Práticas de letramento nas classes multisseriadas da escola Cristo Rei - Abaetetuba-PA - FERREIRA, Sheila de Nazaré Silva (2019)
This article, which has the theme "Literacy Practice in the multisseriate classes of the school municipal Cristo Rei, in the municipality of Abaetetuba-PA ", emerged from the concern of analyzing how teachers of multisseriate classes develop practices literacy with students of the 2nd and 3rd year of Elementary School, at Cristo Rei School. The article comprises a case study carried out in this school with one teacher and two students of the same class. Based on research done, it was found that there are many the difficulties faced by teachers and students in acquiring reading and writing skills; but the existence of these classes has contributed significantly to the training and education peasants and students served in this modality of teaching. During the interview it became clear that, even with all the limitations faced, in relation to resources, family support among others, the teacher does her job in the best way possible, in order to contribute to the development of students.